In vitro protective effect of Celergen, a bioactive marine compound, on interleukin-6-related invasiveness of pancreatic cancer - Catanzaro, Roberto; Celep, Gulcin; Zerbinati, Nicola; Papacharalambous, Michael; Nagpal, Ravinder; Marotta, Francesco; Rastmanesh, Reza; Milazzo, Michele; Lorenzetti, Aldo; Bertuccelli, G; Sollano, J (Acta Biomedica Atenei Parmensis, 2014)
The purpose of this study was to assess the effect of Celergen, a marine nutraceutical, against tumor cell invasion in human pancreatic cancer cell line (PSN-I). High invasive clone (HI) and low invasive clone (LI) were established from wild type PSN-l cell line after a repeated invasion assay test. The invasive ability of HI cells and the level of IL-6 in the conditioned medium of HI cells was significantly higher than that one of LI cells but both these parameters were significantly reduced by the addition of Celergen (p